1980
DOI: 10.1136/sti.56.6.355
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of serum penicillin concentrations after single doses of benzathine and benethamine penicillins in young and old people.

Abstract: SUMMARY In a comparative kinetic study of the serum concentrations of two penicillin complexes-medium-long-acting (benethamine penicillin) and long-acting (benzathine bipenicillin)-after a single injection in young adults and elderly people, the following results were confirmed statistically: (a) age was a major factor in the variations in serum penicillin concentrations and in their persistence in the serum; (b) the penicillin was absorbed faster in young than in elderly subjects even when a long-acting compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Dube administered oral penicillin or intramuscular phenethicillin (a penicillin derivative) to five ambulatory older subjects (age range, 64–90 years) and showed that serum levels did not differ from those reported in the literature for young adults 48 . Other studies have confirmed these earlier findings 49 , 50 . In elderly patients, penicillin would be indicated for infections caused by Streptococcus pneumoniae, Streptococcus bovis, Streptococcus pyogenes , viridans group streptococci, Neisseria meningitidis, Listeria monocytogenes, Treponema pallidum , and anaerobic bacteria except the Bacteroides fragilis group.…”
Section: Pharmacology and Pharmacokinetics Of Antibioticsmentioning
confidence: 56%
“…Dube administered oral penicillin or intramuscular phenethicillin (a penicillin derivative) to five ambulatory older subjects (age range, 64–90 years) and showed that serum levels did not differ from those reported in the literature for young adults 48 . Other studies have confirmed these earlier findings 49 , 50 . In elderly patients, penicillin would be indicated for infections caused by Streptococcus pneumoniae, Streptococcus bovis, Streptococcus pyogenes , viridans group streptococci, Neisseria meningitidis, Listeria monocytogenes, Treponema pallidum , and anaerobic bacteria except the Bacteroides fragilis group.…”
Section: Pharmacology and Pharmacokinetics Of Antibioticsmentioning
confidence: 56%
“…Most of these studies suggested that maintaining blood concentrations of 0.03 IU/mL up to 7 days after the injection occurred in most nonpregnant adults. One study suggested that mean BPG concentrations were adequate 10-13 days following a single dose of 2.4 million units of BPG among most of 40 nonpregnant healthy adults [89], whereas another study found subtreponemicidal concentrations in 3 of 12 nonpregnant adults studied 7 days after BPG dose [90]. A study of 25 healthy pregnant women reported that 9 of 25 women had serum levels <0.018 µg/mL 7 days following an intramuscular dose of 2.4 million units of BPG [91].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that patients in the later stages of disease have more established, relatively slowly progressing disease in which organisms divide at a slower rate, and therefore a longer duration of therapy is needed. Since a single injection of benzathine penicillin provides penicillinemia for 2-3 weeks [22], recommended treatment with three weekly injections of benzathine penicillin does not triple or even double the duration of therapy. Furthermore, because of the relatively low serum levels attained with multiple doses, weekly dosing of benzathine penicillin does not result in levels of drug that are dramatically elevated over the levels attained following a single injection.…”
Section: Current Therapeutic Recommendationsmentioning
confidence: 99%